Effects of Starvation on Brain Short Neuropeptide F-1, -2, and -3 Levels and Short Neuropeptide F Receptor Expression Levels of the Silkworm, Bombyx mori - Nagata, Shinji; Matsumoto, Sumihiro; Nakane, Tomohiro; Ohara, Ayako; Morooka, Nobukatsu; Konuma, Takahiro; Nagai, Chiaki; Nagasawa, Hiromichi (Frontiers in Endocrinology, 2012)
In our previous report, we demonstrated the possibility that various regulatory neuropeptides influence feeding behavior in the silkworm, Bombyx mori. Among these feeding-related neuropeptides, short neuropeptide F (sNPF) exhibited feeding-accelerating activity when injected into B. mori larvae. Like other insect sNPFs, the deduced amino acid sequence of the cDNA encoding the sNPF precursor appears to produce multiple sNPF and sNPF-related peptides in B. mori. The presence of three sNPFs, sNPF-1, sNPF-2, and sNPF-3, in the brain of B. mori larvae was confirmed by direct MALDI-TOF mass spectrometric profiling. In addition, all three sNPFs are present in other larval ganglia. The presence of sNPF mRNA in the central nervous system (CNS) was also confirmed by RT-PCR. Semi-quantitative analyses of sNPFs in the larval brain using MALDI-TOF MS further revealed that brain sNPF levels decrease in response to starvation, and that they recover with the resumption of feeding. These data suggest that sNPFs were depleted by the starvation process. Furthermore, food deprivation decreased the transcriptional levels of the sNPF receptor (BNGR-A10) in the brain and CNS, suggesting that the sNPF system is dependent on the feeding state of the insect and that the sNPF system may be linked to locomotor activity associated with foraging behavior. Since the injection of sNPFs accelerated the onset of feeding in B. mori larvae, we concluded that sNPFs are strongly related to feeding behavior. In addition, semi-quantitative MS analyses revealed that allatostatin, which is present in the larval brain, is also reduced in response to starvation, whereas the peptide level of Bommyosuppressin was not affected by different feeding states.